IMPLEMENTASI E-GOVERNMENT DALAM PELAYANAN PINDAH KELUAR KOTA/KABUPATEN ATAU PROVINSI DI KELURAHAN BONGKARAN SURABAYA - Amalia Ramadhani Rachmad; Susi Hardjati (Journal Publicuho, 2024)
Surabaya is the provincial capital and one of the largest cities in Indonesia. Because of its high migration flow, immigrants and migrants in Surabaya require population administration services. In compliance with Presidential Regulation Number 6 of 2001, the Surabaya City Population and Civil Registration Service, which organized population administration (adminduk), implemented e-government by offering a variety of conveniences, including administrative service innovations like e-Klampid, which later became Klampid New Generation (KNG). The purpose of this study is to investigate how e-government is being implemented in provinces, cities, and districts with innovative programs like Bongkaran Village, and Surabaya City's Klampid New Generation (KNG) program. Researchers employ qualitative approaches in their work; these methods are qualitative and descriptive in nature. The PAN Ministerial Decree No. 63 of 2003, which addresses the Principles of Public Services, is the theoretical foundation for this study. The result of the research found that Bongkaran Subdistrict's e-government implementation, which utilizes the KNG program for inter-city/regency or provincial transfer services, is performing well in terms of service procedure, cost, time, officer competency, facilities, and infrastructure indicators.